Economic evaluation of algae biodiesel based on meta-analyses. Issue 7 (9th August 2017) - Zhang, Yongli; Liu, Xiaowei; White, Mark A.; Colosi, Lisa M.
ABSTRACT: The objective of this study is to elucidate the economic viability of algae-to-energy systems at a large scale, by developing a meta-analysis of five previously published economic evaluations of systems producing algae biodiesel. Data from original studies were harmonised into a standardised framework using financial and technical assumptions. Results suggest that the selling price of algae biodiesel under the base case would be $5.00–10.31/gal, higher than the selected benchmarks: $3.77/gal for petroleum diesel, and $4.21/gal for commercial biodiesel (B100) from conventional vegetable oil or animal fat. However, the projected selling price of algal biodiesel ($2.76–4.92/gal), following anticipated improvements, would be competitive. A scenario-based sensitivity analysis reveals that the price of algae biodiesel is most sensitive to algae biomass productivity, algae oil content, and algae cultivation cost. This indicates that the improvements in the yield, quality, and cost of algae feedstock could be the key factors to make algae-derived biodiesel economically viable.